Antibiofilm activity of secondary metabolites of sponge-associated bacterium Alcanivorax sp. from the Red Sea - Jamal, Mamdoh T.; Satheesh, Sathianeson (Frontiers in Marine Science, 2022)
Sponge-associated bacteria are well known source of unique and diverse natural products with potentially new biological activities. In this study, a rarely occurring sponge-associated bacterium from the genus Alcanivorax was isolated from the sponge Siphonochalina siphonella and subjected to extraction of metabolites. Metabolites were extracted from the culture supernatant and biomass of the bacterium using the solvent extraction method. Extracts were evaluated for antibacterial and antibiofilm activity against 5 different biofilm-forming bacteria isolated from the microfouling assemblage. The crude extracts were subjected to chemical profiling to identify their composition using GC-MS. The results obtained shows mild to strong antibacterial activity of the extracts against the biofilm-forming bacteria with the MIC of 3.125 mg ml-1. Percentage inhibition of biofilm formation range from 46% to 71%. Compounds detected in GC-MS analysis are mostly fatty acids and its derivatives that include compounds with known antibiofilm activity such as tetradecanoic acid, dodecanoic acid and hexadecanol from culture supernatant extract while eicosane, Hexadecanoic acid, methyl ester, and Hexadecanoic acid, ethyl ester from biomass extract. Molecular docking analysis of the compounds from the bacterial extracts confirms their potential antibiofilm properties. The result indicated that Alcanivorax sp. associated with the sponge possess relevant antibiofilm activity and may serve as a novel source of secondary metabolites with the application as antibiofilm agents.